Bolivia : Statistical Annex. (IMF Staff Country Reports; Country Report, 2001)
This paper provides statistical data of macroeconomic flows, national accounts, production, and employment, combined public sector, financial sector, and external sector. They are listed as follows: gross domestic product by expenditure, mining reserves and production, investment in petroleum exploration, consumer prices, public sector employment, operations of the central government, monetary surveys, selected interest rates, open market bills, balance of payments, exports by principal products, direction of trade, effective exchange rate, summary accounts of the central bank, imports by economic category, and so on.